2021
DOI: 10.36067/jbis.v3i1.90
|View full text |Cite
|
Sign up to set email alerts
|

Meningkatkan penerapan SAK EMKM dengan persepsi usaha dan kesiapan pelaku UMKM

Abstract: UMKM (Micro Small Medium Enterprises) plays an important role in developed countries, particularly in Indonesia, which works absorbing many workers to reduce the number of unemployment. This research aims to examine the effect on the application of accounting recording systems, accounting comprehensions, business perceptions, and UMKM preparedness in implementing SAK EMKM. The objects of the research are UMKM in Yogyakarta. The respondents were 120 UMKM owners. This study is using multiple regression analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
3
1
4
Order By: Relevance
“…SAK EMKM can be applied to financial reports if MSME actors already have accounting knowledge and understand how to prepare good and correct financial reports. Thus the results of this study undermine previous research conducted by (Darmasari & Wahyuni, 2020;Muslihah Rositasari et al, 2022;Purnomo & Adyaksana, 2021). • Through the use of an accounting information system, it has been shown that the education level has no direct impact on the performance of MSMEs.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…SAK EMKM can be applied to financial reports if MSME actors already have accounting knowledge and understand how to prepare good and correct financial reports. Thus the results of this study undermine previous research conducted by (Darmasari & Wahyuni, 2020;Muslihah Rositasari et al, 2022;Purnomo & Adyaksana, 2021). • Through the use of an accounting information system, it has been shown that the education level has no direct impact on the performance of MSMEs.…”
Section: Discussioncontrasting
confidence: 84%
“…The findings of this study, however, may potentially undermine other studies by (Sovia, 2022) and (Karsiati & Maskudi, 2022) that claim that accounting expertise influences MSMEs' performance indirectly via the use of an accounting information system. (Darmasari & Wahyuni, 2020;Muslihah Rositasari et al, 2022;Purnomo & Adyaksana, 2021). • Through the use of an accounting information system, it has been shown that the education level has no direct impact on MSMEs' performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Questionnaires were given to 110 SMEs owners who manage culinary businesses. We chose The type of culinary business because several previous findings stated that most SMEs have a culinary business [11,13]. This research went through two stages of testing, namely data testing and hypothesis testing.…”
Section: Methodsmentioning
confidence: 99%
“…Proses untuk mencatat dan menyajikan informasi dan kondisi keuangan yang digunakan untuk membuat keputusan (Purnomo & Adyaksana, 2021). Manajemen keuangan wirausaha harus lebih simple, sederhana dan aplikatif, namun tetap dalam ketentuan yang standard dan lazim.…”
Section: Pendahuluanunclassified